PENGARUH INOVASI PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE ANDROID SAMSUNG - Pranatalion, Reinardus; Tjahjono, Endro; Mulyati, Diana Yuli (Jurnal Dinamika Administrasi Bisnis, 2016)
This study aimed to discover and prove the influence of product innovation, brand and prices buying decision against Samsung Android. Sources of data used comes from a questionnaire distributed to 100 respondents from various Colleges in the city of Surabaya. The questionnaire measured using likert Scale and the data analysis technique chosen is the tecnique of multiple linear regression analysis. The results showed that the product innovation, brand image, and the price of the product significantly affects the dependent variable is the purchase decision because of F obtained at the number 11,395 and is supported with a significance level (p) < 0,05. Product innovation, brand image, and the price of the product is able to influence the level of dependene variable that purchase decision 26,3% and the remaining 64,7% of purchase decision are influenced other variables in out of the study